Pengaruh Penggunan Kata Gaul dalam Bahasa Inodesia terhadap Kemampuan Berbahasa Siswa SMA - Manalu, Devi Rosalinda; Manik, Lolona; Tarigan , Sri Winensi; Patrisa Panjaitan, Yunilawati; Daulay, Muhammad Anggie Januarsyah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The use of slang words in Indonesian has become a common phenomenon among teenagers. In the context of using the Indonesian language, the use of slang words can affect the language proficiency of high school students. This study aims to explore how the use of slang words in Indonesian affects the language proficiency of high school students. This research employs a qualitative research design with a Case Study approach. The study uses Huberman's Analysis, which involves three main stages: data reduction, data display, and conclusion drawing/verification. The results of the study indicate that the use of slang words in Indonesian can interfere with high school students' ability to use Indonesian properly and correctly. This is due to the shortening of words, the addition of letters to standard words, the use of letters, and the use of numbers in writing, which can hinder the growth and development of the Indonesian language. Therefore, it is important to increase high school students' awareness of the importance of using proper and correct Indonesian and to instill a love for the Indonesian language among teenagers